APPLICATION OF INNOVATIVE SOLUTIONS OF DRUM DRYERS IN INDUSTRY (Journal of Science-Innovative Research in Uzbekistan, 2024)
The utilization of drum dryers in industrial settings represents a cornerstone in the thermal treatment of granular materials. These devices are pivotal in facilitatinga myriad of heat and mass exchange processes critical for various industrial applications. From absorption to catalytic reactions, drum dryers play a multifacetedrole in enhancing efficiency and productivity across diverse industries. One of the foremost applications of drum dryers lies in facilitating efficient drying processes.Through mechanisms such as heat exchange and evaporation, these innovative solutions expedite the removal of moisture from granular materials, thereby optimizing production processes. Moreover, the integration of dispersed catalysts enables catalytic processes within the drum dryer, further enhancing its versatility and effectiveness. Furthermore, drum dryers are instrumental in driving various chemical reactions essential for industrial processes. Whether it involves burning, adsorption, or dissolution of solids, these devices provide a controlled environment conducive to accelerating these reactions. Additionally, their design allows for seamless integration with other industrial processes, thereby streamlining operations and bolstering overall efficiency. In essence, the application of innovative solutions in drum dryers represents a paradigm shift in industrial thermal treatment. By harnessing a diverse array of heat and mass exchange processes, these devices pave the way for enhanced productivity, energy efficiency, and cost-effectiveness in industrial operations. As industries continue to evolve, the role of drum dryers in facilitating innovation and optimization remains indispensable